The Effect of Control Resolution on the Usability of Color-Tunable Lighting Systems. Issue 1 (2nd January 2019) - Hu, Wenye; Davis, Wendy
ABSTRACT: Color-tunable lighting systems with inappropriate resolutions may confuse end-users and prevent them from easily specifying their desired colors. To improve the design of color-tunable systems, a psychophysical experiment explored the independent and interacting effects of hue, saturation, and luminance control resolutions on usability. Three criteria—efficiency, effectiveness, and satisfaction—were used to evaluate these effects. Results showed that combinations of middle-range hue resolution and saturation resolution facilitated the greatest usability. When luminance control was independent of hue and saturation control, luminance resolution did not significantly impact usability.